Momentum and reversal: The role of short selling - ZHU, Zhaobo (Institutional Knowledge at Singapore Management University, 2019)
This paper investigates the relation between short selling and momentum. We document that a consistent momentum strategy that buys lightly shorted winners and sells heavily shorted losers exhibits strong short-term momentum and no long-term reversal. In contrast, an inconsistent momentum strategy that buys heavily shorted winners and sells lightly shorted losers experiences weak short-term momentum and persistent long-term reversal. Our results are robust after controlling for firm characteristics, proxy for short-sale constraints, and investor sentiment, as well as an exogenous shock (the Taxpayer Relief Act of 1997). These findings present a new challenge to existing theories of momentum that rely solely on investor underreaction and overreaction.